Pancreatic islets: methods for isolation and purification of juvenile and adult pig islets - Brandhorst, H; Johnson, PRV; Brandhorst, D (Springer, 2016)
The current situation of organ transplantation is mainly determined by the disbalance between the number of available organs and the number of patients on the waiting list. This obvious dilemma might be solved by the transplantation of porcine organs into human patients. The metabolic similarities which exist between both species made pancreatic islets of Langerhans to that donor tissue which will be most likely transplanted in human recipients. Nevertheless, the successful isolation of significant yields of viable porcine islets is extremely difficult and requires extensive experiences in the field. This review is focussing on the technical challenges, pitfalls and particularities that are associated with the isolation of islets from juvenile and adult pigs considering donor variables that can affect porcine islet isolation outcome.